Targeted transfection and expression of hepatitis B viral DNA in human hepatoma cells. - Liang, T J (1993)
A soluble DNA carrier system consisting of an asialoglycoprotein covalently linked to poly-L-lysine was used to bind DNA and deliver hepatitis B virus (HBV) DNA constructs to asialoglycoprotein receptor-positive human hepatoma cells. 4 d after transfection with surface or core gene expression constructs, HBsAg and HBeAg in the media were measured to be 16 ng/ml and 32 U/ml per 10(7) cells, respectively. Antigen production was completely inhibited by the addition of an excess of asialoorosomucoid. On the other hand, asialoglycoprotein receptor-negative human hepatoma cells, SK-Hep1, did not produce any viral antigens under identical conditions after incubation with HBV DNA complexed to a conjugate composed of asialoorosomucoid and poly-L-lysine. Using a complete HBV genome construct, HBsAg and HBeAg levels reached 16 ng/ml and 16 U/ml per 10(7) cells, respectively. Northern blots revealed characteristic HBV RNA transcripts including 3.5-, 2.4-, and 2.1-kb fragments. Intracellular and extracellular HBV DNA sequences including relaxed circular, linear and single stranded forms were detected by Southern blot hybridization. Finally, 42-nm Dane particles purified from the spent cultures medium were visualized by electron microscopy. This study demonstrates that a targetable DNA carrier system can transfect HBV DNA in vitro resulting in the production of complete HBV virions.